From undergraduate to entrepreneur : The driving force of success through financial management - Mohd Hafizuddin Hiew Abdullah @ Hiew Yeap Seng (2015)
This case study goes in depth on how the founder controlling the limited paid up capital and success in build up relatively successful micro-business from nothing.